GEOCHEMICAL EVIDENCE OF ISLAND-ARC ORIGIN IN VOLCANIC ROCKS OF CENTRAL SUMATERA - Iskandar Zulkarnain (JURNAL RISET GEOLOGI DAN PERTAMBANGAN, 2014)
Abstract. Geochemical study on volcanic in Lampung and Bengkulu regions proposed a preposition that the western part of Sumatera is formed by a separated fragment with island-arc character and does not belong to continental margin of Eurasia. Geochemical signatures of western and eastern volcanic in Central Sumatera have confirmed the preposition indicated by evidences of existing island-arc tectonic environment on the western volcanic and both island-arc and continental tectonic environments on the eastern volcanic. Besides that, the geochemical data in this region have revealed the third tectonic environment reflecting development of back-arc tectonic setting in the geological history of the island. The island-arc tectonic setting is marked by higher ratio of (Ti/Ce)N, varying from 0.15 to 0.3, but in narrow ratio of (Ta/Nb)N, between 1.0 to 1.5, while the Active Continental Margin tectonic environment is characterized by wide range of (Ta/Nb)N ratio, ranging from 1.2 to 2.8 but with ratio of (Ti/Ce)N less than 0.1. The back-arc basin tectonic setting is marked by high ratio of (Ti/Ce)N, up to more than 0.8. The results are made based on rock chemistry analysis including major, trace and rare earth elements.